2016
DOI: 10.3389/fmicb.2016.00278
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Fermentation with Selected Immobilized Non-Saccharomyces Yeast for Reduction of Ethanol Content in Wine

Abstract: The average ethanol content of wine has increased over the last two decades. This increase was due to consumer preference, and also to climate change that resulted in increased grape maturity at harvest. In the present study, to reduce ethanol content in wine, a microbiological approach was investigated, using immobilized selected strains of non-Saccharomyces yeasts namely Starmerella bombicola, Metschnikowia pulcherrima, Hanseniaspora osmophila, and Hanseniaspora uvarum to start fermentation, followed by inoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
100
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(114 citation statements)
references
References 33 publications
3
100
0
3
Order By: Relevance
“…Previous studies (Canonico, Comitini, Oro, & Ciani, ; Contreras, Curtin, & Varela, ; Contreras et al, ; Gobbi et al, ; Varela, Barker, Tran, Borneman, & Curtin, ) have reported a significant reduction in ethanol yield (0.3%–1.7% v/v) when using non‐ Saccharomyces and S. cerevisiae strains in co‐inoculated or sequential cultures. The use of M. pulcherrima co‐inoculated with S. cerevisiae in the pilot‐scale production of Merlot wines resulted in 1.0% v/v lower ethanol content compared to wines fermented by S. cerevisiae alone (Varela et al, ).…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Previous studies (Canonico, Comitini, Oro, & Ciani, ; Contreras, Curtin, & Varela, ; Contreras et al, ; Gobbi et al, ; Varela, Barker, Tran, Borneman, & Curtin, ) have reported a significant reduction in ethanol yield (0.3%–1.7% v/v) when using non‐ Saccharomyces and S. cerevisiae strains in co‐inoculated or sequential cultures. The use of M. pulcherrima co‐inoculated with S. cerevisiae in the pilot‐scale production of Merlot wines resulted in 1.0% v/v lower ethanol content compared to wines fermented by S. cerevisiae alone (Varela et al, ).…”
Section: Resultsmentioning
confidence: 93%
“…At lower levels (below 50 mg/L), acetaldehyde can contribute pleasant fruity aromas to a wine. As for comparison, Varela et al (2017) and Canonico et al (2016) reported that wines produced with M. pulcherrima showed higher concentrations of ethyl acetate, total esters, total higher alcohols, and total sulfur compounds Table 1. a,b,c different letters for the results in every specific day of alcoholic fermentation indicate significant differences between values (p < .05) and benzyl alcohol (9.7-11.2 mg/L) were detected in wines produced by the activity of S. cerevisiae, in both individual and sequential inoculations (samples CER, MET+CER, and MET+BAY+CER).…”
Section: The Impact Of Used Yeast Strains On the Composition Of Volmentioning
confidence: 99%
See 1 more Smart Citation
“…Other authors (Canonico et al . ) have shown that the M. pulcherrima yeast species is a good candidate for this purpose.…”
Section: Discussionmentioning
confidence: 99%
“…Besides having a role in shaping wine flavour profile, M . pulcherrima has also shown potential as a mixed starter culture for reducing alcohol concentration during wine fermentation (Canonico et al ., ; Contreras et al ., ; Quiros et al ., ).…”
Section: Metschnikowia Sppmentioning
confidence: 99%